Effect of Surface Hydrophobicity on the Adsorption of a Pilus-Derived Adhesin-like Peptide - Yang, Yu (Langmuir : the ACS journal of surfaces and colloids, 2022)
Bacterial colonization of abiotic surfaces such as those of medical implants, membrane filters, and everyday household items is a process of tremendous importance for public health. Bacteria use adhesive cell surface structures called adhesins to establish contact with abiotic surfaces. Among them, protein filaments called type IV pili are particularly important and found in many Gram-negative pathogens such as Pseudomonas aeruginosa. Understanding the interaction of such adhesin proteins with different abiotic surfaces at the molecular level thus represents a fundamental prerequisite for impeding bacterial colonization and preventing the spread of infectious diseases. In this work, we investigate the interaction of a synthetic adhesin-like peptide, PAK128-144ox, derived from the type IV pilus of P. aeruginosa with hydrophilic and hydrophobic self-assembled monolayers (SAMs). Using a combination of molecular dynamics (MD) simulations, quartz crystal microbalance with dissipation monitoring (QCM-D), and spectroscopic investigations, we find that PAK128-144ox has a higher affinity for hydrophobic than for hydrophilic surfaces. Additionally, PAK128-144ox adsorption on the hydrophobic SAM is furthermore accompanied by a strong increase in α-helix content. Our results show a clear influence of surface hydrophobicity and further indicate that PAK128-144ox adsorption on the hydrophobic surface is enthalpically favored, while on the hydrophilic surface, entropic contributions are more significant. However, our spectroscopic investigations also suggest aggregation of the peptide under the employed experimental conditions, which is not considered in the MD simulations and should be addressed in more detail in future studies